Endoscopic Extraction of Fasciola Hepatica: A Case Report - Ünal, N.; Tanriverdi Çayci, Y.; Ecemiş, O.; Bektaş, A.; Hökelek, M. (Refik Saydam National Public Health Agency (RSNPHA) turkhijyen@rshm.gov.tr, 2015)
Fasciola hepatica infection is a zoonosis mostly encountered in the sheep-raising countries. The early phase F. hepatica infection is characterised by fever, abdominal pain and eosinophilia. The biliary obstruction and icterus are rarely caused by F. hepatica. Our case was a 22-years old female, from Giresun, a north coast city of Turkey, who applied because of icterus and abdominal pain. To analyse the problem abdominal US and laboratory tests was performed which showed dilation in the proximal of choledochal and tubuler echogenites and elevated hepatic enzymes. Endoscopic retrograde cholangiopancreatography showed minimal dilatation of intrahepatic bile ducts and heterogenous filling defect in the hilus. Biliary sphincterotomy had been applied and F. hepatica had been removed by balloon catheter. This case report showed that endoscopic retrograde cholangiopancreatography (ERCP) has an important role in the diagnosis and the treatment of biliary fascioliasis.
Keywords: Biliary Obstruction; ERCP; Fasciola Hepatica